Non-indigenous and Invasive Freshwater Species on the Atlantic Islands of the Azores Archipelago - Costa, Ana C.; Balibrea, Ana; Raposeiro, Pedro M.; Santos, Sofia; Souto, Martin; Gonçalves, Vítor (Frontiers in Ecology and Evolution, 2021)
Freshwater systems in remote oceanic islands are particularly vulnerable to biological invasions due to the reduced and unique diversity. The case of freshwater ecosystems in the Azores Archipelago is especially relevant considering the youth and remoteness of the islands and their natural un-connectivity. This study presents a review of the introduction and presence of non-indigenous freshwater species in Azores, using all available records to date, retrieved from different sources as historical records, paleoenvironmental reconstructions, published records and field data from two decades of Water Framework Directive monitoring programs. At least 132 non-indigenous freshwater species have successfully established in Azores, belonging to several taxonomic groups: cyanobacteria (10), synurophytes (1), desmids (1), diatoms (20), plants (41), invertebrates (45), amphibia (2) and fishes (12). These introductions, intentional or non-deliberate, have been occurring since the establishment of the first human settlers on the archipelago impacting freshwater ecosystems. Reported introductions in the Azores were intentional fish stocking in some lakes but non-deliberate introductions have recently increased, mostly related to ornamental or aquaria trade. Most of non-indigenous species have been accidentally introduced in Azores mostly by transport-contaminant (51%) associated to aquarium trade or associated with agricultural products. In Azores, the highest number of non-indigenous species occurs in the largest and most populated island: São Miguel (116), followed by Flores (68), an island where freshwater habitats are particularly important. Plants constitute the more representative group of introduced species in all islands, but invertebrates, diatoms and fishes are also well established in most islands. Among invertebrates, non-indigenous arthropods are the most well-established group in all islands except in the smallest Corvo island. Many non-indigenous species will likely benefit from a climate changing scenario magnified by globalization that increases the probability for the movement of tropical and subtropical species to the Azores considering present trends on international trading, importations, and enhanced connectivity of the archipelago by an increasing number of flights and shipping. Also, augmented connectivity among islands is likely to enhance dispersal of non-indigenous freshwater species within the archipelago as accidental transportation seems to be an important pathway for the non-indigenous freshwater species present in the Azores.